Impact Of Bank Risk On Bank Performance In Indonesian Commercial Banks: The Moderating Role Of Corporate Governance - Annaas Azzumar Rahman; Ilham Abadi; Henny Setyo Lestari; Susy Muchtar (UNIVED Press, 2026)
This study analyzes the impact of bank risk exposures, including Environmental, Social, and Governance (ESG) Risk, Credit Risk, Liquidity Risk, Market Risk, Operational Risk, and Capital Adequacy Ratio (CAR), on the financial performance of commercial banks in Indonesia, as measured by Return on Assets (ROA). Driven by increasing regulatory pressure and market demands for sustainable financial practices, this research also explores the moderating role of Corporate Governance in strengthening or weakening the impact of these risks on bank performance. The research employs a quantitative approach using panel data regression with EViews 9 software, utilizing secondary data from 10 commercial banks listed on the Indonesia Stock Exchange during the period 2020–2024. Data sources include annual reports, sustainability reports, OJK publications, and Bloomberg ESG Disclosure Scores. The findings reveal that ESG Risk, Liquidity Risk, Market Risk, and CAR have a significant impact on ROA, whereas Credit Risk, Operational Risk, and control variables (Bank Size and Asset Growth) do not have a significant impact. An interesting finding of this study is the positive yet insignificant relationship between Credit Risk and ROA, which contrasts with conventional literature. This result is presumed to be influenced by credit restructuring policies and government stimulus during the COVID-19 pandemic, as well as variations in risk management strategies across banks. Meanwhile, Market Risk, as measured by the Net Interest Margin (NIM), shows a significant negative impact on ROA, contrary to the initial hypothesis, indicating intense market competition and fluctuating interest income within Indonesia’s banking sector. The moderating effect of Corporate Governance on the relationship between risk and performance is not fully significant, except for its interaction with Market Risk, which demonstrates the potential to enhance risk management effectiveness. These findings underscore the importance of strengthening governance and risk management to improve the resilience and profitability of the national banking sector.